1999
DOI: 10.1038/sj.cdd.4400495
|View full text |Cite
|
Sign up to set email alerts
|

Activation of a low pH-dependent nuclease by apoptotic agents

Abstract: Intracellular acidification caused by agents such as UV(C), etoposide or ceramide accompanies the progression of apoptosis. It is suggested that cellular acidosis may set favorable conditions for a dormant, low pH-dependent (acidic) nuclease, which could be involved in intranucleosomal genome degradation, a hallmark of programmed cell death. Here we show that exposure of HL-60 cells to acidotic/ apoptotic agents results in the several-fold activation of a novel low pH-dependent (acidic) nuclease activity, as r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
24
0

Year Published

2002
2002
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(26 citation statements)
references
References 52 publications
2
24
0
Order By: Relevance
“…Zymography assays demonstrated that the 32-kDa protein is likely to be the nuclease responsible for generation of TUNEL-positive cells after g-irradiation. These results resemble those in UV(C)-irradiation of HL60 cells (17). However, when HL60 cells were irradiated with a high dose of g-rays, and/or incubated after irradiation, there was a tendency for DNase II and acid phosphatase in the nuclear extract to decrease.…”
Section: Discussionsupporting
confidence: 50%
See 2 more Smart Citations
“…Zymography assays demonstrated that the 32-kDa protein is likely to be the nuclease responsible for generation of TUNEL-positive cells after g-irradiation. These results resemble those in UV(C)-irradiation of HL60 cells (17). However, when HL60 cells were irradiated with a high dose of g-rays, and/or incubated after irradiation, there was a tendency for DNase II and acid phosphatase in the nuclear extract to decrease.…”
Section: Discussionsupporting
confidence: 50%
“…Zymography assays were done for endonuclease activity (17). Twelve percent of the polyacrylamide gels were copolymerized with calf thymus DNA (0.2 mg/ml) and stored overnight at 48C and 20 ml nuclear extracts were mixed with equal volumes of the sample buffer and separated at 100 mV for 90 min.…”
Section: Zymography Assay For Endonuclease Activitymentioning
confidence: 99%
See 1 more Smart Citation
“…40 Regarding the nuclear amount of acidic endonucleases, it is important to stress that the activity of DNase II-like 29-31 kDa polypeptides identified in fibroblasts and also that of low-pHdependent nucleases unrelated to DNase II in HL60 and HeLa cells have been shown to be upregulated upon exposure to diverse acidotic/apoptotic stimuli such as anoxia, UV or etoposide. 37,38 Nonetheless, since this upregulation was not sufficient to cause any deleterious effects when caspase activation and intracellular acidification were downregulated, Famulski et al 38 postulated that the acidic nuclease upregulation alone was not a sufficient prerequisite for the execution of apoptosis. In this context, other cellular targets for the apoptosis-related cytosolic acidification should be sought ( Figure 5).…”
Section: Intracellular Acidification In Apoptosismentioning
confidence: 99%
“…Although the importance of cytosol acidification is still controversial, mounting evidence suggests that cytosol acidification at least contributes to cytochrome c release, caspase and endonuclease activation, and apoptosis in some cell systems. Reduction of the cytosolic pH (intracellular acidification) due to proton channel inhibition can induce apoptosis, and conversely, prevention of cytosol acidification can block apoptosis [12,[17][18][19][20][21]. However, it remains unclear how cytosol acidification facilitates apoptosis.…”
Section: Introductionmentioning
confidence: 99%